AB0480 Folic acid supplementation delays clinical improvement in rheumatoid arthritis patients treated with methotrexate. (12th June 2018) - Sulli, A.; Pizzorni, C.; Paolino, S.; Tomatis, V.; Ghio, M.; Ruaro, B.; Cutolo, M.
Abstract : Background: Methotrexate (MTX) is the disease-modifying anti-rheumatic drug (DMARD) most commonly used in the treatment of rheumatoid arthritis (RA), and folic acid (FA) supplementation is usually employed to prevent MTX-related adverse effects. 1 However, the need of FA supplementation remains controversial, as it might influence the efficacy of MTX therapy. 2 Objectives: The aim of this retrospective study was to evaluate the effects of FA supplementation on both efficacy and safety of low-dose MTX in the treatment of RA patients. Methods: 120 RA patients (mean disease duration 11±30 months, mean age 61±13 SD years), according to ACR criteria, 3 who started low-dose MTX treatment were retrospectively evaluated. Patients were not complaining of serious diseases other than RA. Two groups of patients were selected: patients supplemented with FA (#58) and patients not-supplemented with FA (#62). MTX dose, prednisone dose, disease activity (DAS28), and adverse event (AE) were recorded at 3, 6, 9, 12, 24, 36, and 48 months. At baseline, MTX mean dose was 8.3±1.9 and 8.1±1.4 mg/weekly, prednisone mean dose was 7.4±3.1 and 5.3±3.2 mg/daily, and mean DAS28 was 5.1±1.2 and 4.8±1.1, respectively for both groups. The patients were followed-up until MTX discontinuation, new DMARD/BiologicDMARD addition, need for FA supplementation, or after 48 months of therapy (mean follow-up 40±20 months). The maximum MTX dose administered during the follow-up was 15 mg/weekly. Statistical analysis was performed by non parametric tests. Results: DAS28 decreased in both groups during the study. However, DAS28 was found significantly lower (p<0.04) in patients without FA supplementation, when compared with patients taking FA supplementation, at months 3, 6, 9, and 12. Patients without FA supplementation required significantly lower (p<0.01) doses of both prednisone and MTX during the follow-up. AEs were observed in 26% of patients with FA supplementation, as well as in 43% of patients without FA supplementation. The difference was statistically significant (p=0.049). No difference in AE type was observed between the groups (mainly, transaminase or mean red blood cell volume elevation, oral mucositis, urinary tract infections). AEs have been successfully managed in the majority of cases by either discontinuing MTX for two weeks or adding FA if required. Conclusions: In RA patients taking low-dose MTX, FA supplementation decreases the efficacy of the treatment, delaying the clinical responsiveness. The lack of administration of FA increases the risk of AEs; however, by considering the benign type of AEs usually observed in this subset of patients, the treatment with low doses of MTX might be started without FA supplementation, and the FA administration deferred until AE appearance. References: [1] Shea B, et al. Cochrane Database Syst Rev. 2013May 31;(5):CD000951. [2] Arabelovic S, et al. J Am Coll Nutr2007;26:453–5. [3] Aletaha D, et al. Arthritis Rheum2010;62:2569–81. Disclosure of Interest: None declared